2011
DOI: 10.1007/s11634-011-0096-5
|View full text |Cite
|
Sign up to set email alerts
|

Model-based clustering and segmentation of time series with changes in regime

Abstract: Mixture model-based clustering, usually applied to multidimensional data, has become a popular approach in many data analysis problems, both for its good statistical properties and for the simplicity of implementation of the Expectation-Maximization (EM) algorithm. Within the context of a railway application, this paper introduces a novel mixture model for dealing with time series that are subject to changes in regime. The proposed approach, called ClustSeg, consists in modeling each cluster by a regression mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
85
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 20 publications
0
85
0
Order By: Relevance
“…For example, Wedel (2002) and Grun and Leisch (2008) considered MoLE densities for modeling concomitant variables; Ingrassia et al (2012) showed it to be related to cluster-weighted modeling; and Chamroukhi et al (2009Chamroukhi et al ( , 2010, and Same et al (2011) applied it to fit, classify, and cluster time-series data, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wedel (2002) and Grun and Leisch (2008) considered MoLE densities for modeling concomitant variables; Ingrassia et al (2012) showed it to be related to cluster-weighted modeling; and Chamroukhi et al (2009Chamroukhi et al ( , 2010, and Same et al (2011) applied it to fit, classify, and cluster time-series data, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Each curve represents the consumed power by the switch motor during each switch operation and the aim is to predict the state of the switch given a new operation data, or to cluster the times series to discover possible defaults. These data were studied in Chamroukhi (), Chamroukhi, Samé, Govaert, and Aknin (), Chamroukhi et al (, ), and Samé, Chamroukhi, Govaert, and Aknin (). Figure e shows n = 120 curves where each curve consists of m = 564 observations and Figure f shows n = 146 curves where each curve consists of m = 511 observations.…”
Section: Introductionmentioning
confidence: 99%
“…Many functional clustering methods have been developed over the last decade. These methods can usually be separated into two categories: nonparametric methods using specific distances or dissimilarities between curves (Dabo-Niang et al, 2007), and mixture-model-based methods (Samé et al, 2011;Jacques and Preda, 2014). The collected curves can be multivariate, leading to a large representation space like in (Cheifetz et al, 2013) for change-point detection based on a specific curve modeling.…”
Section: Introductionmentioning
confidence: 99%